The Neural Stem Cell Properties of PKD2L1+ Cerebrospinal Fluid-Contacting Neurons in vitro - Wang, Shuo; He, Yuqi; Zhang, Huiqian; Chen, Li; Cao, Liang; Yang, Leiluo; Wang, Chunqing; Pan, Yujie; Tang, Qian; Tan, Wei; Dou, Xiaowei; Li, Qing (Frontiers in Cellular Neuroscience, 2021)
Cerebrospinal fluid-touching neurons (CSF-cNs) exist in the region surrounding the central canal of the spinal cord, which locate in the adult neurogenic niche. Previous research showed that CSF-cNs expressed the molecular markers of immature neural cells in vivo. Here, we explored the potential of CSF-cNs as neural stem cell in intro. We first found that PKD2L1+ CSF-cNs, isolating by FACS using the molecular marker PKD2L1 of CSF-cNs, expressed neural stem cells markers like Nestin, Sox2, and GFAP by immunofluorescence staining. PKD2L1+ CSF-cNs were able to form neurospheres and passaged in vitro. Immunofluorescence staining showed that the neurospheres forming by PKD2L1+ CSF-cNs also expressed neural stem cell markers Nestin, Sox2 and GFAP. The neurospheres expressed proliferation markers Ki67 and PCNA by immunofluorescence staining, indicating that the neurospheres forming by PKD2L1+ CSF-cNs were proliferative. The neurospheres, forming by CSF-cNs, had the ability of differentiation into neurons, astrocytes, and oligodendrocytes. Collectively, our data suggested that PKD2L1+ CSF-cNs have the properties of neural stem cells in vitro and may provide a promising approach for the repair of spinal cord injury.